2016
DOI: 10.1111/jocn.13285
|View full text |Cite
|
Sign up to set email alerts
|

The personal experience of living with chronic heart failure: a qualitative meta‐synthesis of the literature

Abstract: Nurses must have a personal knowledge of the experiences and needs of the patients. To do this, nurses should create care environments that promote an exchange of experiences and knowledge between the nurse and the patient and family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0
26

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(120 citation statements)
references
References 59 publications
3
91
0
26
Order By: Relevance
“…This can contribute to fragmented care, difficulty navigating care providers, and poor patient/ caregiver experiences. 18 Patient-centred and seamless care requires integration of services and collaboration between care providers, as defined by the shared-care model. 18,19 A substantial proportion of patients, attending the HFCs represented in this survey, do not have a PCP.…”
Section: Current State: Models Of Hf Clinic (Hfc)-based Care In Canadamentioning
confidence: 99%
“…This can contribute to fragmented care, difficulty navigating care providers, and poor patient/ caregiver experiences. 18 Patient-centred and seamless care requires integration of services and collaboration between care providers, as defined by the shared-care model. 18,19 A substantial proportion of patients, attending the HFCs represented in this survey, do not have a PCP.…”
Section: Current State: Models Of Hf Clinic (Hfc)-based Care In Canadamentioning
confidence: 99%
“…Falk and colleagues have suggested that patients with heart failure depend on others because of functional deterioration from various symptoms, express appreciation for being supported, and encourage and promote self‐care. Conversely, if patients feel that support from surroundings is a burden, this may lead to a decrease in self‐esteem (Olano‐Lizarraga, Oroviogoicoechea, Errasti‐Ibarrondo, & Saracibar‐Razquin, ). Basically, participants in this study autonomously lived with heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Heart failure has a major influence on patient's emotional, physical, spiritual and social dimensions. This day-to-day uncertainty of living with HF influences the well-being of the patient and the family (18). Heart failure has been described as more malignant than many of the most common types of cancer, such as prostate-, breast-, bladder-, and colorectal cancer (19).…”
Section: Heart Failurementioning
confidence: 99%
“…Each patient has a personal experience of their illness, which might or might not be similar to other patients' experiences. Therefore, it is important that health care professionals who meet these patients try to understand what impact HF has on each individual patient and that they adapt the care and communication to each individual (18).…”
Section: Coping Strategiesmentioning
confidence: 99%